Budaya Belajar Mahasiswa Selama Bulan Ramadhan dalam Perspektif Nilai-Nilai Islam : Student Learning Culture During the Month of Ramadan from the Perspective of Islamic Values - Ninda, Rafa Maisa; Putri, Naila Ghaitsa; Rahmat, Anye Irawati; Budiman, Silvi Nadia; Suresman, Edi (Litera Academica Publishing, 2026)
This study aims to describe the learning culture of students during Ramadan and analyze the meaning of learning activities as part of worship in the perspective of Islamic values. This study uses a descriptive method with a qualitative approach through observation and interviews with students who continue to attend lectures during Ramadan. The results show that Ramadan affects students' learning rhythms, particularly in the form of changes in sleep patterns, decreased energy, and challenges with concentration during daytime lectures. These conditions pose various academic challenges, but students are able to adapt through time management strategies, gradual task completion, and prioritization based on deadlines. In addition, learning activities are interpreted as a form of worship when based on sincere intentions and an orientation to seek knowledge as part of moral and spiritual responsibility. The values of patience, discipline, trustworthiness, and self-control are internalized in learning practices during Ramadan, so that the learning process is not only understood as an academic obligation, but also as a means of strengthening students' spirituality and character.